Field-based physical fitness assessment in preschool children: A scoping review - Ke, Dandan; Maimaitijiang, Remili; Shen, Shaoshuai; Kishi, Hidetada; Kurokawa, Yusuke; Suzuki, Koya (Frontiers in Pediatrics, 2022)
Physical fitness, which can be measured using various health- and skill-related components, is an important indicator of child development and health status. This study undertakes a scoping review on physical fitness assessment methods in preschool children to summarize the most widely used field-based physical fitness batteries and specific test items for preschool children. A search of the literature in English was undertaken using two major electronics databases, which yielded 76 literatures that met the inclusion and exclusion criteria. These literatures took the quantitative indicators of physical fitness as the outcome variables in 3–6-year-old children. This review found that of these 76 literatures analyzed, 71.1% came from Europe and 89.5% were published after 2010. The results showed six physical fitness test batteries, with the assessing FITness in PREschoolers (PREFIT) battery is the most widely used, and specific test items such as body mass index (BMI), standing long jump, handgrip, one-leg stance, sit and reach, 20 m shuttle run test (SRT)-PREFIT, and 4 × 10 m SRT are widely used in corresponding components. Therefore, we recommend that an international standard for some specific test items should be developed for preschool children to facilitate more widespread adoption and promote physical fitness assessment for preschool children.